Communicating about Undocumented Immigration Issues: Is Your Target Audience Bilingual? - Shuyang Qu; Alexa J. Lamm; Joy N. Rumble (Journal of Applied Communications, 2017)
Due to the large number of undocumented immigrants working in the agricultural and natural resources industry, and recent discussions regarding immigration reform in the United States, agricultural communicators need to understand public opinion of undocumented immigrants and the factors that influence public opinion surrounding immigration issues in order to provide effective information to target audiences. Immigration has often been associated with linguistic diversity since the majority of immigrants speak a language other than English. To understand how linguistic differences impact public opinion, and how to communicate with audiences expressing diverse linguistic preferences, this study used an online survey design to examine the differences in attitudes toward immigration issues and information channel preferences between individuals who are bilingual and those who are not bilingual. Results from 503 Florida residents, representative of the population, indicated that non-bilingual respondents had a significantly more negative attitude toward immigration issues than bilingual respondents. In addition, bilingual respondents preferred to receive information through a website significantly more than non-bilingual respondents. The results imply agricultural communicators should recognize their target audiences’ language ability and create messages about immigration specifically for bilingual and non-bilingual audiences. Bilingual websites should be created to disseminate immigration messages to engage bilingual audiences.
Keywords: Bilingual; Construal Level Theory; Information Channels; Public Opinion Undocumented Immigration